The Role of Islamic Educational Philosophy in Shaping the Character of Educators and Students: A Literature Review on the Concept of Religious Moderation - Wahyuningsih, Sri Wulan; Harliawan; Nuriyah, Dwi; Hikmah, Siti Fatukhatul; Supian (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: This paper aims to analyze the essential role of Islamic Educational Philosophy (IEP) as a normative and operational foundation in shaping the character of both educators and students. The topic is relevant because character formation is a core objective of Islamic education, which aspires to develop the insan kamil through balanced spiritual, intellectual, and social growth. Background Problems: The main problem examined is how IEP provides a philosophical basis that directs character formation in pedagogical attitudes and educational practices. Novelty (optional): This study emphasizes the dual function of IEPconceptual and practical in shaping educator and student character, an aspect that previous studies have not systematically integrated. Research Methods: This research employs a literature review with a descriptive-analytical approach using primary and secondary sources related to IEP and character education. Finding/Results: The findings show two key mechanisms: (1) IEP offers a theoretical foundation for educators by emphasizing Islamic life goals (sa‘adah al-dārayn) and prophetic attributes ṣiddīq, amānah, tablīgh, and faṭānahas professional moral principles and exemplary conduct. (2) IEP shapes students’ character through curriculum orientation and learning methodologies that prioritize righteous habituation, such as justice, tolerance, discipline, and responsibility. Conclusion: The study concludes that strengthening IEP is crucial to ensuring coherence between philosophical ideals and educational practices. The implication is the need to reinforce IEP courses in Islamic teacher education institutions to optimize the alignment between educator character and value transmission.